Assessment of therapeutic response in ankylosing spondylitis patients undergoing anti-tumour necrosis factor therapy by whole-body magnetic resonance imaging - Brandlhuber, Martina; Godau-Kellner, Patrizia; Kellner, Herbert; Horng, Annie; Theisen, Daniel; Glaser, Christian; Brandlhuber, Bernhard; Reiser, Maximilian; Weckbach, Sabine (European radiology, 2013)
Multifocal musculoskeletal inflammation is common in ankylosing spondylitis (AS) and is effectively treated by expensive anti-TNF (tumour necrosis factor) therapy. This study evaluated assessment of response by whole-body (WB) MRI compared with clinical assessment in AS patients during etanercept therapy.